Investigation of Coulomb-induced coupling in semiconductor nanostructures using 2D Fourier-Transform-Spectroscopy - Meier, Torsten; Kuznetsova, Irina; Thomas, Peter; Zhang, Tianhao; Cundiff, Steven T. (International Quantum Electronics Conference)
Two-Dimensional Fourier-Transform-Spectroscopy (2DFTS) is a novel method for the experimental investigation of many-body interactions in semiconductor nanostructures [1]. It displays directly the heavy-hole (hh) and light-hole (lh) excitonic transitions in III-V-quantum wells along the main diagonal of a two-dimensional plot which is spanned by the excitation energy −ħωτ and the emission energy ħωτ. In addition, characteristic signatures due to continuum excitations appear as well as mixed peaks in off-diagonal positions resulting from various couplings. Using a one-dimensional tight-binding model which contains the correct selection rules we compute 2DFTS in the coherent χ(3)-limit. By comparing theoretical spectra resulting from different orders in the Coulomb interaction we can clearly identify the influence of the many-particle interaction on the various signatures that are visible in the spectrograms. The distribution of the peak heights, their magnitude, and their lineshape are of particular interest. Co-circularly polarized excitation pulses are considered.

Experimental and theoretical studies of exciton correlations using optical two-dimensional fourier transform spectroscopy - Meier, Torsten; Zhang, Tianhao; Li, Xiaoqin; Cundiff, S.T.; Mirin, R. P.; Kuznetsova, Irina; Thomas, P. (Quantum Electronics and Laser Science Conference)
Many-body correlations of excitons in semiconductors are explored experimentally with two-dimensional Fourier transform spectroscopy and modeled by a microscopic coherent χ(3) theory beyond the Hartree-Fock approximation with qualitative agreements under different excitation conditions.

Multidimensional ultrafast spectroscopy special feature: polarization-dependent optical 2d fourier transform spectroscopy of semiconductors - Meier, Torsten; Zhang, Tianhao; Kuznetsova, Irina; Li, Xiaoqin; Mirin, R. P.; Thomas, Peter; Cundiff, S.T. (Proceedings of the National Academy of Sciences)
Optical 2D Fourier transform spectroscopy (2DFTS) provides insight into the many-body interactions in direct gap semiconductors by separating the contributions to the coherent nonlinear optical response. We demonstrate these features of optical 2DFTS by studying the heavy-hole and light-hole excitonic resonances in a gallium arsenide quantum well at low temperature. Varying the polarization of the incident beams exploits selection rules to achieve further separation. Calculations using a full many-body theory agree well with experimental results and unambiguously demonstrate the dominance of many-body physics.

Coherent Semiconductor Optics - Meier, Torsten; Thomas, Peter; Koch, Stephan W.

Autobiographisches Schreiben im Roman "Rot" von Uwe Timm - Anfang und Ende einer Autorschaft - Müller, Inez (Autobiographisches Schreiben in der deutschsprachigen Gegenwartsliteratur, Bd. 2: Grenzen der Erinnerung)

Self-Organizing System - Fuchs, Christian (Encyclopedia of Governance)

Antiglobalization - Fuchs, Christian (Encyclopedia of Governance)

Informationalism - Fuchs, Christian (Encyclopedia of Governance)

Anarchy - Fuchs, Christian (Encyclopedia of Governance)

ICTs and society: The Salzburg Approach: Towards a Theory for, about, and by Means of the Information Society. ICT&S Research Paper No. 3 - Hofkirchner, Wolfgang; Fuchs, Christian; Raffl, Celina; Schafranek, Matthias; Sandoval, Marisol; Bichler, Robert

The Urgent Need for Change: Rethinking Knowledge and Management - Fuchs, Christian; Blachfellner, Stefan; Bichler, Robert (Knowledge Management: Innovation, Technology and Cultures. Proceedings of the 2007 International Conference on Knowledge Management)

Tuning the threshold voltage of organic field-effect transistors by an electret encapsulating layer - Scharnberg, M.; Zaporojtchenko, V.; Adelung, R.; Faupel, F.; Pannemann, C.; Diekmann, T.; Hilleringmann, Ulrich (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Electro-thermo-mechanical analytical modeling of multilayer cantilever microactuator - Jiang, Jianliang; Hilleringmann, Ulrich; Shui, Xiaoping (Sensors and Actuators A: Physical)
Keywords: Electrical and Electronic Engineering; Metals and Alloys; Surfaces; Coatings and Films; Condensed Matter Physics; Instrumentation; Electronic; Optical and Magnetic Materials

Nonlinear Identification of Complex Systems Using Radial Basis Function Networks and Model Order Reduction - Wiegand, C.; Hedayat, C.; John, W.; Radic-Weissenfeld, Lj.; Hilleringmann, Ulrich (2007 IEEE International Symposium on Electromagnetic Compatibility)

6I-3 Low-Cost Transceiver Unit for SAW-Sensors Using Customized Hardware Components - Scholz, P.; Dierkes, M.; Hilleringmann, Ulrich (2006 IEEE Ultrasonics Symposium)

Zensurverfahren gegen Giuseppe Verdis "Don Carlo" vor der Römischen Inquisition - Höink, Dominik (Die Musikforschung)
Einen exzeptionellen Sonderfall eines Inquisitionsverfahrens im Rom des 19. Jahrhunderts stellt die Verhandlung von Giuseppe Verdis "Don Carlo" dar. Auf der Grundlage der Akten aus dem Archiv der Glaubenskongregation wird das Verfahren nachgezeichnet und in einem editorischen Anhang das Gutachten dargeboten. Ersichtlich wird an diesem Verfahren eine Facette des kirchlichen Umgangs mit liberalen Ideen zur Zeit Pius IX.
Keywords: Music

Microscopic modeling of photoluminescence of strongly disordered semiconductors - Bozsoki, P.; Kira, M.; Hoyer, W.; Meier, Torsten; Varga, I.; Thomas, P.; Koch, S.W. (Journal of Luminescence)
A microscopic theory for the luminescence of ordered semiconductors is modified to describe photoluminescence of strongly disordered semiconductors. The approach includes both diagonal disorder and the many-body Coulomb interaction. As a case study, the light emission of a correlated plasma is investigated numerically for a one-dimensional two-band tight-binding model. The band structure of the underlying ordered system is assumed to correspond to either a direct or an indirect semiconductor. In particular, luminescence and absorption spectra are computed for various levels of disorder and sample temperature to determine thermodynamic relations, the Stokes shift, and the radiative lifetime distribution.

Signatures of Many-Particle Correlations in Two-Dimensional Fourier-Transform Spectra of Semiconductor Nanostructures - Kuznetsova, I.; Thomas, P.; Meier, Torsten; Zhang, T.; Li, X.; Mirin, R.P.; Cundiff , S. T. (Solid state communications)
On the basis of a microscopic theory, the signatures of many-particle correlations in Two-Dimensional Fourier-Transform Spectra (2D-FTS) of semiconductor nanostructures are identified and compared to experimental data. Spectra in the photon energy range of the heavy-hole and light-hole excitonic resonances show characteristic features due to correlations, which depend on the relative polarization directions of the excitation pulses.

Gottesdienst-Orte. Handbuch Liturgische Topologie. Günter Ruddat zum 60. Geburtstag

Unerhörte Erhörungen - Präludien zu einer musikalischen Religionspädagogik - Schroeter-Wittke, Harald (Vom Psalter zum Pop. Musik in Kultur und Leben)